PATTERNS OF DEFORMATION AND FRACTURE OF CONCRETE UNDER RE MALOTSYKLOVYH NAVANTAZHUVAN CENTRAL COMPRESSION - and (Municipal economy of cities. Series: «Economy science», 2013)
Results of research of the physical nature of a concrete deforming and destruction in conditions of repeated low cyclic loadings the central compression have given possibility to receive the mathematical dependences, allowing to define low cyclic fatique of concrete and forecasting its stressed-strained state at any stages of loading.